Strategi Guru Penerapan Penguatan Pendidikan Karakter pada Pembelajaran Tematik SD Negeri Babad 1 Masa Covid-19 - Angga Ahmad Syaichun Najib; Khusnul Fajriyah; Sunan Baedowi (STKIP Andi Matappa Pangkep, 2022)
The background that prompted this research was to describe the teacher's strategy in Strengthening Character Education in Thematic Learning at SD Negeri Babad 1 during the Covid-19 Pandemic, and to describe the impact of the teacher's strategy in Strengthening Character Education in Thematic Learning at SD Negeri Babad 1 during the Covid-19 Pandemic. 19. This type of research is qualitative research. The data collection procedure was carried out by observation, interview, and documentation techniques. The results of the analysis from teacher and student observations, interviews with principals, teachers and students of SD Negeri Babad 01 have shown that the implementation of teacher strategies in strengthening character education in thematic learning during the covid-19 pandemic, the results obtained are that grade 1 to grade 6 teachers conduct morning habituation, linking learning models and approaches, forming small groups, and providing opportunities for students. The teacher's strategy has an impact on students behaving more politely, politely, with noble character and honest personality. Students are also more courageous and active in expressing opinions when learning takes place. In addition, students can reflect their nationalist attitudes and love for the motherland.